2008
DOI: 10.1080/09638280701456112
|View full text |Cite
|
Sign up to set email alerts
|

The patient's view of recovery: An emerging tool for empowerment through self-knowledge

Abstract: RPE uncovers the life contexts that underlie patients' subjective beliefs about the meaning of being able to perform various types of activities. RPE might be applied in clinical practice and research to explore the idiosyncratic aspects of disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…While clinicians consistently sought early imagined recovery of comprehension and expression, “a cerebral recovery choice pathway,” patients tended to prefer early imagined recovery in eating, bathing, and toileting functions, “a physical recovery choice pathway.” These preference differences are supported by earlier studies [27, 28], further supporting the expectation that the two groups have different outlooks about priorities in functional recovery.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…While clinicians consistently sought early imagined recovery of comprehension and expression, “a cerebral recovery choice pathway,” patients tended to prefer early imagined recovery in eating, bathing, and toileting functions, “a physical recovery choice pathway.” These preference differences are supported by earlier studies [27, 28], further supporting the expectation that the two groups have different outlooks about priorities in functional recovery.…”
Section: Discussionsupporting
confidence: 81%
“…Differences in subjective appraisals [13, 19, 28, 32, 33] highlight the ideographic and nonontological nature of meaning, where the QoL implications of activity limitation are driven in part through each person’s internal explanations of external life contexts as they understand them [31]. Various individuals and groups of people logically judge the relative importance of recovering through different objective frames of reference, subjective standards of comparison, and personal reference points [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was one of the few where the meaning of a daily occupation was targeted in a clinical context, and the findings indicated that cooking was more highly evaluated than the two other activities. Another study, focusing on recovery among patients in physical rehabilitation, reported that eating, bathing, and going to the toilet were their most valued activities (10).…”
Section: Introductionmentioning
confidence: 99%
“…Functional independence measure (FIM) items arranged into domains by meaning are not necessarily grouped in the same ways as FIM items arranged into domains by ontology. 6 When creating domains of meaning, people use various strategies that differ dramatically. Some link activities performed in sequence, such as toilet transfers with toileting (from the activities of daily living (ADL) and mobility domains, respectively).…”
mentioning
confidence: 99%